Student Perceptions of the Implementation of Project Based Learning (PjBL) in English Learning for Non English Program Student - Efriza, Dony; Yelia; Adimarta, Teguh (International Journal of Language Pedagogy, 2025)
Project Based Learning (PjBL) is a learning model that uses a project approach. This research is a descriptive research. The instrument of this research is survey which developed by some indicators; motivation, interest, real-world, learn more lecture, very beneficial, and enjoyble. The survey distribute by useing google form in collecting data. The sample of this research is economic education students of FKIP Jambi University batch 2023 who take English courses. The results of data analysis stated that students’ perceptions of the implementation of project based learning (PjBL) were very positive. These study shows that 62% of students respond strongly agree and 38% of students respond agree in conducting Project Based Learning (PjBL). Most students strongly agree that PjBL serve real-world project and it useful for their life. This aspect influence motivation, interest, and enjoyble in learning. These results conclude that Project Based Learning (PjBL) has a positive impact on the English learning process for non-English program students which providing real-life English project.